Analysis of Crack Initiation in Hot Forging Process with the Support of the Digital Image Correlation System - Łukasz Lisiecki; Paulina Lisiecka-Graca; Nikolaos E. Karkalos (Applied Sciences)
The limits of plastic deformation without failure are considered to be a measure of formability and can be estimated by the standard tests. However, the mechanical states observed during commonly used compression tests are similar to those observed in many bulk deformation processes, with an additional advantage of those tests having the possibility of applying large deformations without the risk of the appearance of necking (in tension) or material reorientation (in torsion). Thus, this study presents the results of modified compression tests under conditions of a real forging process, since knowledge of the geometrical parameters of the tools and samples makes it possible to determine the areas of stress concentration which contribute to the formation of controlled cracks. The digital image correlation system (DIC) was used to analyze the deformation parameters that lead to achieving the critical values of fracture criterion; simulations were additionally performed to confirm the reliability of predicting the location and the critical moment just before failure in the forging process under consideration. After the accuracy of the model was verified, this approach was applied to a case of backward extrusion, also correctly predicting the locations with high probability of fracture.